Analisis Penggunaan Kontrasepsi IUD pada Ibu-Ibu Post Sectio Caesarea - Hasanah, Hafizotun; Chodijah, Siti; Sari, Yemmy Putri (JURNAL KESEHATAN TERAPAN, 2025)
Contraception is a health service program to prevent or delay pregnancy for women. The target form of contraception is post-CS mothers who have given birth. For this reason, post-CS mothers who are over 30 years old and already have more than 2 children are advised to use long-term contraception in post-CS mothers at RSIA Az-Zahra Palembang in 2024. This research method uses an analytical method with a case control approach by looking at medical record data at RSIA Az-Zahra. The results of this study The frequency distribution of respondents who used IUD contraception was 72 respondents (50%) and respondents who did not use IUD contraception were 72 respondents (50%). Most of the respondents, namely 79 respondents (54.9%) had non- risk parity, most of the respondents, namely 83 respondents (57.6%) did not work, most of the respondents, namely 76 respondents (52.8%) were knowledgeable. The conclusion is that we as health workers can continue to provide education and counseling to post-CS mothers in choosing contraceptives, especially IUDs, by using counseling media that are easy for the public to understand.